Chronology and documentary handbook of the State of Illinois - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1978)
A chronology of historical events from 1659-1977, a biographical outline of politicians and personalities, and selected documents.
Bibliography: p. [137]-140. and index.
Keywords: Illinois -- History -- Chronology; Illinois -- Biography; Illinois -- History -- Sources; Illinois -- History